Immunophenotyping of Peripheral Blood, Lymph Node, and Bone Marrow T Lymphocytes During Canine Leishmaniosis and the Impact of Antileishmanial Chemotherapy - Santos, Marcos Ferreira; Alexandre-Pires, Graça; Pereira, Maria A.; Gomes, Lídia; Rodrigues, Armanda V.; Basso, Alexandra; Reisinho, Ana; Meireles, José; Santos-Gomes, Gabriela M.; Pereira da Fonseca, Isabel (Frontiers in Veterinary Science, 2020)
Dogs are a major reservoir of Leishmania infantum, etiological agent of canine leishmaniosis (CanL) a zoonotic visceral disease of worldwide concern. Therapeutic protocols based on antileishmanial drugs are commonly used to treat sick dogs and improve their clinical condition. To better understand the impact of Leishmania infection and antileishmanial drugs on the dog's immune response, this study investigates the profile of CD4+ and CD8+ T cell subsets in peripheral blood, lymph node, and bone marrow of sick dogs and after two different CanL treatments. Two CanL groups of six dogs each were treated with either miltefosine or meglumine antimoniate combined with allopurinol. Another group of 10 clinically healthy dogs was used as control. Upon diagnosis and during the following 3 months of treatment, peripheral blood, popliteal lymph node, and bone marrow mononuclear cells were collected, labeled for surface markers CD45, CD3, CD4, CD8, CD25, and intracellular nuclear factor FoxP3, and T lymphocyte subpopulations were immunophenotyped by flow cytometry. CanL dogs presented an overall increased frequency of CD8+ and CD4+CD8+ double-positive T cells in all tissues and a decreased frequency of CD4+ T cells in the blood. Furthermore, there was a higher frequency of CD8+ T cells expressing CD25+FoxP3+ in the blood and bone marrow. During treatment, these subsets recovered to levels similar to those of healthy dogs. Nevertheless, antileishmanial therapy caused an increase of CD4+CD25+FoxP3+ T cells in all tissues, associated with the decrease of CD8+CD25−FoxP3− T cell percentages. These findings may support previous studies that indicate that L. infantum manipulates the dog's immune system to avoid the development of a protective response, ensuring the parasite's survival and the conditions that allow the completion of Leishmania life cycle. Both treatments used appear to have an effect on the dog's immune response, proving to be effective in promoting the normalization of T cell subsets.